Project management as a subject in university studies for information and documentation in Latin America - Cobo Serranog, Silvia; Arquero Aviles, Rosario (BiD (Barcelona, Spain), 2014)
Objective: This paper examines the current offering of the subject Project Management in bachelor's and master's degrees in information and documentation in Ibero-America, focusing on the countries Argentina, Bolivia, Brazil, Chile, Colombia, Costa Rica, Cuba, the Dominican Republic, Ecuador, Guatemala, Jamaica, Mexico, Nicaragua, Panama, Paraguay, Peru, Portugal, Puerto Rico, El Salvador, Spain, Uruguay and Venezuela. The paper analyses different features of the subject in these degree courses to provide a general overview. Methodology: A search obtained information about the offering of the subject Project Management in degree courses at an international level and the results were examined by university and by degree course. The university curricula were then analysed according to specific selection criteria, as outlined in the paper, and the researchers corresponded by email with the teaching staff responsible for these courses. Various parameters were studied and then recorded in a database. Finally, the results were analysed. Results: After the universities, degrees and subjects had been identified and selected according to the research criteria, it was observed that 77% of the entire offering that included the degree course subject Project Management was to be found in first-cycle (bachelor's) degrees, and that Mexico, Colombia and Spain were the countries where the offering was greatest. The study also showed that Project Management was a compulsory subject in 86 % of the sample analysed. Adapted from the source document.